The impact of hard Brexit on Polish exports - Jakub Borowski; Jakub Olipra; Paweł Błaszyński (International Journal of Management and Economics, 2018)
The decision of the United Kingdom (UK) to leave the European Union (EU) is unprecedented, especially considering the recent trend in the global economy toward economic integration. There is a multitude of research concerning the implications of economic integration; however, research in the field of disintegration is scarce. Brexit serves as an interesting case study to investigate the effects of economic disintegration. The implications for trade are especially fascinating as trade liberalization is one of the most important benefits of economic integration. Existing studies focus mainly on Brexit's impact on the UK's exports and imports, while less attention has been paid to Brexit's effects on the trade of other countries. The main objective of our research is to estimate Brexit's influence on Polish exports. We present several possible scenarios of future trade relations between the UK and the EU and assume that, at least in the nearest-future post-Brexit scenario, trade under the World Trade Organization rules is most likely. This will result in the imposition of tariffs on trade between the UK and the EU members, including Poland. In our research, we used the real exchange rate of the Polish zloty against the British pound as a proxy for the changes in price competitiveness of Polish exports due to the imposition of tariffs. We find that in the first year after Brexit, the dynamics of Polish exports to the UK will decrease due to the imposition of customs duties by 1.3 percentage points (pp) and by 0.1 pp when it comes to total Polish exports. This paper contributes to the discussion on the effects of disintegration on trade. We propose a new method for assessing changes in trade volume due to increase of trade barriers.
Keywords: F13; F14; F15; F17; 650; Brexit; international trade; European integration